Oral and general health behaviours among Chinese urban adolescents - Petersen PE, Jiang H, Peng B, Tai BJ, Bian Z. (Blackwell Synergy, 2008)
The objectives of this study were to measure the association of general and oral health-related behaviours with living conditions and to explore the interrelationships between general and oral health-related behaviours in Chinese urban adolescents